Traffic efficiency of post-earthquake road network in fault region retrofitted by friction core rubber bearing. (October 2021) - Lian, Qiang; Yuan, Wancheng; Yu, Juanya; Dang, Xinzhi
Abstract: The post-earthquake emergency response depends on the traffic efficiency of the transportation network system. The bridge is the key factor affecting the reliability of the transportation network. Due to factors such as low design standards and performance degradation, the bridges built in the early days had low seismic performance. In fault regions, the pulse effect will also increase the seismic demand of the structure. In this paper, a friction core rubber bearing (FCRB) is proposed for seismic retrofit of road network bridge. Then calculate the fragility of bridges with and without retrofit under pulse and non-pulse effect, and the bridge traffic capacity under several road network conditions. The total travel time of the road network is used as a quantitative index of the reliability of the transportation network, and the prioritization of bridge retrofit under the limited budget and the assessment method of road network seismic risk are proposed. By comparing the difference of total travel time of road networks under different working conditions, the influence of pulse effect and the effect of FCRB are analyzed. Finally, a case is given to illustrate the effectiveness of FCRB in retrofitting the road network bridge and the necessity of considering the pulse effect. The results show that: it is necessary to consider the influence of pulse effect in road network risk assessment with high earthquake magnitude; the bridge retrofit prioritization takes into account the bridge traffic flow and the bridge traffic capacity, which is easy to calculate and can identify the critical bridges that have an important influence on traffic efficiency; with the increase of earthquake magnitude, the seismic risk of road network presents a geometric increase trend; FCRB can significantly reduce the road network seismic risk, and the seismic risk can be reduced by more than 50% if 20 bridges are retrofitted; with the increase in the number of retrofitted bridges, the decreasing trend of the annual seismic risk changes from fast to slow, and finally tends to be flat, which verifies the effectiveness of the retrofit prioritization.